Wind Tunnel Testing Of A Joined-wing Aircraft Model With Additive Manufactured Components - Teo, Zhen Wei (2016)
In this paper, the suitability of using additive manufacturing to fabricate aircraft test model components for use in wind tunnel testing will be reported. The purpose is to investigate the aerodynamic performance of a joined-wing aircraft model under subsonic flow conditions. The resulting test model wings are both complex and thin, and hence significant challenges surround the use of conventional machining due to vibrations from the cutting tools and non-trivial wing thinness. In contrast, additive manufacturing technique was able to overcome these fabrication issues, with a faster turnaround time, less material wastage and ease of design. However, surface finishing and cost issues associated with the additive manufactured components were observed during the study. In particular, significant deflections of the additive manufactured component were observed during testing, which could have explained discrepancies found between the experimental and numerical simulation results. Nonetheless, possible ways to correct these discrepancies will be described and discussed here.